2016
DOI: 10.1371/journal.pone.0153475
|View full text |Cite
|
Sign up to set email alerts
|

Different Growth and Physiological Responses to Cadmium of the Three Miscanthus Species

Abstract: Miscanthus has been proposed as a promising crop for phytoremediation due to its high biomass yield and remarkable adaptability to different environments. However, little is known about the resistance of Miscanthus spp. to cadmium (Cd). To determine any differences in resistance of Miscanthus to Cd, we examined plant growth, net photosynthetic rate (Pn), activities of anti-oxidant and C4 photosynthetic enzymes, concentrations of Cd in leaves and roots, and observed the chloroplast structure in three Miscanthus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
44
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 54 publications
10
44
1
Order By: Relevance
“…In this real-field experiment, M.×giganteus was shown to be capable of developing and growing in flotation tailings loaded with heavy metals. By far the largest portions of accumulated Pb, Cu and Zn were retained in the roots, which corresponded to data reported for different Miscanthus species grown on metal polluted substrates [29,[44][45][46]. Such pronounced retention of metals by the roots is due to their effective immobilization, mostly within the cell walls of the cortex parenchyma cells, and efficiently prevented transport toward the stele and aerial parts by the Casparian strip [47,48].…”
Section: Discussionsupporting
confidence: 84%
“…In this real-field experiment, M.×giganteus was shown to be capable of developing and growing in flotation tailings loaded with heavy metals. By far the largest portions of accumulated Pb, Cu and Zn were retained in the roots, which corresponded to data reported for different Miscanthus species grown on metal polluted substrates [29,[44][45][46]. Such pronounced retention of metals by the roots is due to their effective immobilization, mostly within the cell walls of the cortex parenchyma cells, and efficiently prevented transport toward the stele and aerial parts by the Casparian strip [47,48].…”
Section: Discussionsupporting
confidence: 84%
“…However, the algal PEP carboxylase activity is mainly anaplerotic and not photosynthetic (Giordano, Norici, Forssen, Eriksson, & Raven, ). Although the impact of cadmium on PEPC activity is not established in C. reinhardtii , it has been shown that Cd inhibits PEPC activity in higher plants like Miscanthus species (Guo et al, ) and Zea mays (Wang, Zhao, Liu, Zhou, & Jin, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, SOD activities of Avicennia marina (a common mangrove species in South China) were decreased by Pb stress [32] and the activities of SOD decreased in Cd-treated L. olgensis leaves, possibly due to the binding of Cd to the thiol groups of the enzymes [21]. Previous studies have shown that spraying SA and other organic acids on tobacco [33], rice (Oryza sativa) [34], or perennial ryegrass [35] plants increases SOD activity. Similar responses in SOD activity were observed in maize leaves at six and then days after 1.0 mmol•L −1 SA treatment, where the copper couple superoxide dismutase (Sod4) transcription increased [36].…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll is highly sensitive to stress and indicates the resistance of plants to stressed environments [41]. Environmental stress may harm the chloroplast structure of plants, inhibiting chlorophyll synthesis [35]. Carotenoid, a cell endogenous antioxidant, also plays an important role in scavenging reactive oxygen species and preventing membrane lipid peroxidation [40].…”
Section: Discussionmentioning
confidence: 99%